Limit load analysis of thick-walled as-fabricated pipe bends under in-plane moment loading and internal pressure. (July 2019) - Sorour, Sherif S.; Shazly, Mostafa; Megahed, Mohammad M.
Abstract: The fabrication of pipe bends by rotary bending results in geometrical imperfections as manifested by cross-sectional ovality and wall thickness variations which affect their load carrying capacity and hence their performance during service. Previous studies ignored the exact distribution of these imperfections and adopted either ideal pipe bend shape (IB) or assumed the distribution these imperfections in their analysis by a simplified assumed shape model (AS). The objective of the present work is to investigate the effect of the presence of the inherited geometrical imperfections as obtained from the rotary pipe bending process of 90° pipe bends including the presence of residual stresses on their load carrying capacities as compared with the IB and AS models. The present work is conducted by means of non-linear finite element modeling considering both material and geometrical non-linearities. Rotary pipe bending process is simulated with basic tooling configuration to obtain the as-fabricated 90° pipe bend after accounting for springback. Results of this step were verified against published experimental results and analytical solutions. The pipe bend was then subjected to different combinations of in-plane moment and internal pressure in order to construct a comparative limit load diagram. The IB model for the pipe bend results in non-conservative results, while AS model results in acceptable results compared to results of the as-fabricated shape. Results have also shown that presence of residual stresses improves the pipe performance under in-plane closing bending moment. Highlights: Ideal pipe bend model provides non-conservative results for limit loads. Tensile tangential residual stresses prevent ovalization at low pressures. Geometrical imperfections lowers limit loads of Annealed As-Fabricated pipe bends. As-Fabricated pipe bend has higher Collapse and Instability Moments.